Attitudes Towards Females in the Oil and Gas Industry in the UAE - Al Khoori, Mohamed Abbas (2011)
Attitude towards women is a very important subject that has been discussed all around the world. Unfortunately, in the Arab countries, a limited number of researches were done on that subject despite the fact that Arabs possess a conservative attitude towards women. This paper described the situation of the attitude towards women around the word but more focus was given to the UAE. In the UAE, a specific industry, Oil and Gas, was studied due to an assumed negative attitude towards women. A 3-page questionnaire was submitted amongst Oil and Gas employees as well as the general public to get a better understanding about the attitude toward women in the region. Women As Managers Scale (WAMS) was used to quantify the attitude towards women and to ultimately find the direction of respondents; whether participants have a positive, neutral or negative attitude towards women. The total number of responses collected was 237 where at least half of them were filled by Oil and Gas employees and the remaining were filled by the public. After receiving the responses, all the data were quantified and fed to SPSS. Using the software, data were analyzed using descriptive statistics, t-tests, means comparison, etc. to measure the attitude towards women against three variables namely: gender, age and nationality. Furthermore, analysis was made on the barrier that impacts females the most in the workforce. Findings were that the Oil and Gas Industry had a rather positive attitude towards women. It was also found that females had a more positive attitude towards women when compared to men. On the other hand, participants from different ages and different nationalities did not have exhibit significant differences in their attitude towards working women. Furthermore, Work-Family Conflict was found to be the biggest barrier inhibiting the advancement of women in the workplace. Based on these findings, short term and long term recommendations were addressed that included having flexible timings for mothers working in the industry.